2012
DOI: 10.5194/sed-4-131-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Geomagnetic jerks characterization via spectral analysis

Abstract: In this study we have applied spectral techniques to analyze geomagnetic field time-series provided by observatories, and compared the results with those obtained from analogous analyses of synthetic data estimated from models. Then, an algorithm is here proposed to detect the geomagnetic jerks in time-series, mainly occurring in the Eastern component of the geomagnetic field. Applying such analysis to time-series generated from global models has allowed us to depict the most important space-time features of t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…As already mentioned above, in the Gufm1 model the B‐splines were chosen of order 4 and the nodes are 2.5 years apart from each other. Nevertheless, the influence of the cubic B‐splines cannot explain all variations present in the shown curve, i.e., the behavior found in our analysis is not at the same time scale [see also Duka et al ., ].…”
Section: Results and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…As already mentioned above, in the Gufm1 model the B‐splines were chosen of order 4 and the nodes are 2.5 years apart from each other. Nevertheless, the influence of the cubic B‐splines cannot explain all variations present in the shown curve, i.e., the behavior found in our analysis is not at the same time scale [see also Duka et al ., ].…”
Section: Results and Interpretationmentioning
confidence: 99%
“…[], from an analysis of error bars in the time occurrence of geomagnetic jerks, suggested the worldwide characteristic of 1969, 1978, and 1991 geomagnetic jerks, while the 1999 event was detected only regionally. In a more recent paper [ Duka et al ., ], it was found that the 1969, 1978, and 1999 events can be considered global events, while the 1991 event has a regional extension. It is interesting to notice that the geomagnetic jerks detected over the 20th century are characterized by a mean repeat time interval of around 9 years, although, thanks to a better ground and satellite data coverage, there is a recent tendency to detect more densely occurrences of jerks.…”
Section: Geomagnetic Jerksmentioning
confidence: 99%
“…In this way, the chaotic nature of the field does not have too large an effect on the possible shorttime extrapolation of the field from the repeat-station observations. As already indicated [Newitt et al 1996], another advantage of frequent re-occupation will be to eventually track rapid changes in secular variation, such as the jerks [e.g., Duka et al 2012]. Finally, the property of ergodicity confirms that both the operation of making time averages at the repeat station and the comparison with analogous time averages at close magnetic observatories or stations for temporal reduction, are appropriate, because of the validity between the exchange of phase space and time averages, as given by Equation (5).…”
Section: Discussionmentioning
confidence: 99%